Level of physical activity of physical education students according to criteria of the IPAQ questionnaire and the recommendation of WHO experts - Pastuszak Anna; Lisowski Krzysztof; Lewandowska Joanna; Buśko Krzysztof (Sciendo, 2014)
Study aim: Systematic physical activity is an effective preventive measure that supports the preservation of physical health and psychological health. Three expressions employed that relate to the work carried out with MET-min/week as a measure of the level of total physical activity are intense activity, moderate activity, and walking. These were applied to students studying Physical Education. In the process, those who failed to meet the requirements for the 'sufficient' level according to IPAQ criteria and as recommended by the WHO were identified.